A PCR-mutagenesis strategy for rapid detection of mutations in codon 634 of the ret proto-oncogene related to MEN 2A. - Godoy Clara; Perinetti Héctor; Pusiol Eduardo; Roqué María; Mayorga Luis S (BMC, 2002)
Abstract Background Multiple endocrine neoplasias type 2A (MEN 2A) is a dominantly inherited cancer syndrome. Missence mutations in the codon encoding cysteine 634 of the ret proto-oncogene have been found in 85% of the MEN 2A families. The main tumour type always present in MEN 2A is medullar thyroid carcinoma (MTC). Only 25% of all MTC are hereditary, and generally they are identified by a careful family history. However, some familial MTCs are not easily detected by this means and underdiagnosis of MEN 2A is suspected. Methods DNA samples from MEN 2A patients were amplified by PCR. The products were incubated with the restriction enzyme Bst ApI or Bgl I. The samples were loaded in non-denaturing 10% Polyacrilamyde Gel and run at 120 volts for 40 min. The gels were stained with 10 μg/ml ethidium bromide, and the bands were visualized under a UV lamp. Results We developed a PCR-mutagenic method to check the integrity of the three bases of the cysteine 634 codon. Conclusion The method can be used to detect inherited mutations in MTC patients without a clear family history. The method is relatively simple to use as a routine test in these patients to decrease the underdiagnosis of MEN 2A. In addition, the assay can be used to screen affected families with any mutation in cysteine 634.